Percutaneous transhepatic techniques for management of biliary anastomotic strictures in living donor liver transplant recipients - Chinmay B Kulkarni; Nirmal K Prabhu; Nazar P Kader; Ramiah Rajeshkannan; Sreekumar K Pullara; Srikanth Moorthy (Indian Journal of Radiology and Imaging, 2017)
Aim: To retrospectively analyze the percutaneous transhepatic techniques and their outcome in the management of biliary strictures in living donor liver transplant (LDLT) recipients. Materials and Methods: We retrieved the hospital records of 400 LDLT recipients between 2007 and 2015 and identified 45 patients with biliary strictures. Among them, 17 patients (37.8%) (Male: female = 13:4; mean age, 36.1 ± 17.5 years) treated by various percutaneous transhepatic biliary techniques alone or in combination with endoscopic retrograde cholangiopancreatography (ERCP) were included in the study. The technical and clinical success of the percutaneous management was analyzed. Results: Anastomotic strictures associated with leak were found in 12/17 patients (70.6%). Ten out of 12 (83.3%) patients associated with leak had more than one duct-duct anastomoses (range, 2–3). The average duration of onset of stricture in patients with biliary leak was 3.97 ± 2.68 months and in patients with only strictures it was 14.03 ± 13.9 months. In 6 patients, endoscopic-guided plastic stents were placed using rendezvous technique, plastic stent was placed from a percutaneous approach in 1 patient, metallic stents were used in 2 patients, cholangioplasty was performed in 1 patient, N-butyl- 2-cyanoacrylate embolization was done in 1 child with biliary-pleural fistula, internal-external drain was placed in 1 patient, and only external drain was placed in 5 patients. Technical success was achieved in 12/17 (70.6%) and clinical success was achieved in 13/17 (76.5%) of the patients. Posttreatment mean time of follow-up was 19.4 ± 13.7 months. Five patients (29.4%) died (two acute rejections, one metabolic acidosis, and two sepsis). Conclusions: Percutaneous biliary techniques are effective treatment options with good outcome in LDLT patients with biliary complications.